'Maymd soldiours or poore schollers': Warfare and self-referentiality in the works of Thomas Nashe. Issue 1 (April 2018) - Sivefors, Per
The present article suggests that war and peace are explored in the works of Thomas Nashe as figures for the condition of the writer. Throughout his career, including his troubles with the authorities and his conflict with Gabriel Harvey, Nashe makes use of the war metaphor in order to elaborate on the condition of authorship. However, war is also a literal presence in Nashe's texts, which frequently reference events like the Spanish Armada or the campaign in Ireland. Thus, the article examines the complex interplay between social reality and self-referential metaphor that characterizes Nashe's use and descriptions of warfare.